MOTIVASI KERJA KARYAWAN UNIT TRANFUSI DARAH PALANG MERAH INDONESIA KOTA YOGYAKARTA - Roselina Kuswandari (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2019)
The problems examined in this study are how efforts should be made to increase the motivation of the employees. The study was conducted at the Blood Transfusion Unit of the Indonesian Red Cross (UPTD PMI) Yogyakarta, aiming at finding what efforts should be made to improve the motivation of the employees.The method used in this research is a close-ended question questionnaire employing a five-point scale of Likert and an open-ended question questionnaire. Data analysis method used is qualitative descriptive analysis. The data used are primary data obtained through questionnaires. Respondents of this study were employees of the blood transfusion unit (UTD PMI) of Yogyakarta city, numbering 35 people. The result shows that the perception of the motivation of the three aspects had an average value (grand mean motivation) of 3.2, which, according to the frequency table, is sufficiently good. Employees would eagerly carry out their jobs due to the satisfaction of their needs consisting of the existences of impulses, achievable hope, and rewards. Data from the open statements reveal there is a tendency from respondents to desire salary adjustment, communication, infrastructures and facilities for their works, safety and comfort while on duty, pleasure from working, and work rules which produce a rise of motivation while working. Research result and conclusion point out that employees’ motivation for working can be improved by conducting evaluation.